Femtosecond multiple filamentation of an optical vortex in the mid-IR wavelength range in fused silica and fluorides. (1st April 2022) - Shlenov, S.A.; Kompanets, V.O.; Dergachev, A.A.; Kandidov, V.P.; Chekalin, S.V.; Soifer, F.I.
Abstract: The results of experimental and theoretical study of the self-action of femtosecond optical vortices in the region of anomalous group velocity dispersion in fused silica and fluorides are presented. Multiple filamentation of an axially asymmetric annular beam with a phase dislocation of topological charge m = 1 at a wavelength of 1800 nm in a LiF crystal is investigated. It is found that for the experimentally recorded intensity profile of a vortex beam with two maxima on the diameter, the critical self-focusing power is approximately two times larger than the critical power of a unimodal Gaussian beam. In pulses with supercritical power in the vicinity of the intensity maxima, two coupled filaments, separated by a phase dislocation, are formed on the annular profile of the optical vortex, which prevents energy exchange during their formation. The length of vortex-beam plasma channels in a single pulse is found to be about 300 μm at a diameter of about 2 μm, which is close to the characteristics of plasma channels in a Gaussian beam.